PENSAR A NIGÉRIA EM HIBISCO ROXO: UMA PROPOSTA DE LEITURA - KARAM, BÁRBARA CHRISTIANE (2023)
This dissertation’s object is the novel Hibisco Roxo, by the Nigerian writer Chimamanda Ngozi Adiche, published in 2011. The work has traces of a postcolonial Nigeria. The book describes a family from Enugu (Nigeria) that lives under the religious precepts of Catholicism imposed by the patriarchal figure. These doctrines lead the father to reject the traditions of his people, setting a limited life for his family without the right to question. Kambili and Jaja travel to her aunt Ifeoma's house in Nsukka, this trip transforms Kambili's way of seeing herself and her country, Nigeria. The theoretical basis for this analysis is "A poesia envenenada de Dom Casmurro" by Roberto Schwarz, from the book Duas Meninas (1997). Schwarz proposes that readings be made in layers, instigating the readers to do a reading beyond the conventional one, being meticulous in the details, so that they may understand the work as a whole from other perspectives.